Understanding Metabolic Remodeling in Mycobacterium smegmatis to Overcome Energy Exigency and Reductive Stress Under Energy-Compromised State - Patil, Varsha; Jain, Vikas (Frontiers in Microbiology, 2021)
Mycobacteria such as Mycobacterium tuberculosis, the causative agent of tuberculosis that annually kills several million people worldwide, and M. smegmatis, the non-pathogenic fast-growing mycobacteria, require oxidative phosphorylation to meet their energy requirements. We have previously shown that deletion of one of the two copies of atpD gene that codes for the ATP synthase β-subunit establishes an energy-compromised state in M. smegmatis. Here we report that upon such deletion, a major routing of electron flux occurs through the less energy-efficient complexes of its respiratory chain. ∆atpD bacterium also shows an increased reduced state which is further confirmed by the overexpression of WhiB3, a major redox sensor. We show a substantial modulation of the biosynthesis of cell wall associated lipids and triacylglycerol (TAG). An accumulation of TAG-containing lipid bodies is further confirmed by using 14C oleate incorporation. Interestingly, the mutant also shows an overexpression of TAG-degrading lipase genes, and the intracellular lipolytic enzymes mediate TAG hydrolysis for their utilization as energy source. We believe that our in vitro energy-depleted model will allow us to explore the critical link between energy metabolism, redox homeostasis, and lipid biosynthesis during ATP-depleted state, which will enhance our understanding of the bacterial adaptation, and will allow us to identify novel drug targets to counter mycobacterial infections.